Factors influencing damage to cerebral white matter in the elderly - Blease, S (2009)
BACKGROUND: White matter hyperintensities (WMH) appearing on magnetic resonance images (MRI) occur in the non-demented and demented elderly. Age is an established risk factor associated with WMH. Other possible risk factors include sex, smoking, hypertension, biochemical markers and genotypes associated with B vitamin status, and APOE ε4 status. WMH have been associated with an increased risk of depression and cognitive dysfunction. OBJECTIVES: To investigate factors associated with WMH 2 to 5 years later in healthy elderly. Measures of cognitive impairment, depression, and brain volume were also evaluated in relation to WMH. METHODS: 155 healthy volunteers (60 to 90 years) were included (49% women). Participants completed approximate yearly examinations including a medical history, cognitive assessment, depression survey, T1 and T2-weighted MRI, blood samples measuring markers and genotypes associated with B vitamin deficiencies, and APOE ε4 status. Associations were investigated by Pearson correlations, followed by linear regression, adjusted for age and sex. RESULTS: Age was positively associated with WMH. Other significant prospective risk factors included systolic blood pressure (SBP) and diastolic blood pressure (DBP). DBP and total WMH were positively associated in hypertensive, but not normotensive participants. Elevated homocysteine was positively associated with WMH within the top tertile. No other factors were significantly associated with WMH. Baseline WMH were negatively associated with follow-up (3 to 5 years) cognitive assessments of executive function and processing speed, and positively associated with depressive symptoms. Furthermore, WMH were positively associated with ventricular cerebrospinal fluid volume and negatively associated with percent brain volume change and grey matter volume, but not white matter volume. CONCLUSIONS: Age is the most striking risk factor associated with WMH; other significant factors include SBP and DBP. Baseline WMH were associated with decreased performance on tests of executive function, processing speed, and increased depressive symptoms. These data suggest that WMH is not a benign process of aging considering the positive associations to hypertension, cognitive impairment, and depression.